2017
DOI: 10.37358/rc.17.8.5764
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral NMR and Micro DSC Study of Artificially Aged Parchments

Abstract: New and artificially aged parchments were studied by unilateral NMR and micro DSC. Samples were obtained by exposing new parchments to 80 °C and alternate 40 and 80% relative humidity for increasing times up to 32 days. The impact of accelerated ageing was assessed by measuring both the proton transverse relaxation times (T 2eff ) and thermodynamic parameters associated with thermal denaturation of fibrillar collagen. Depending on the ageing time, significant structural changes correlated with thermal stabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…This quantitative parameter is the energy required to disrupt the interactions stabilizing the secondary and tertiary structures of the triple helix. It was shown to be very useful in quantifying the effects of damaging factors on chemically unmodified collagen in parchment [36,37,42]. Recently, Carșote et al [25,35] have shown that micro DSC offers both qualitative and quantitative information to also characterize chemically modified collagen in historical leather.…”
Section: Standard Methods Mht Methods Tg/dtg T S (°C) T F (°C) T S (°C)mentioning
confidence: 99%
See 2 more Smart Citations
“…This quantitative parameter is the energy required to disrupt the interactions stabilizing the secondary and tertiary structures of the triple helix. It was shown to be very useful in quantifying the effects of damaging factors on chemically unmodified collagen in parchment [36,37,42]. Recently, Carșote et al [25,35] have shown that micro DSC offers both qualitative and quantitative information to also characterize chemically modified collagen in historical leather.…”
Section: Standard Methods Mht Methods Tg/dtg T S (°C) T F (°C) T S (°C)mentioning
confidence: 99%
“…Effective 1 H spin-spin relaxation T 2eff measurements have been measured using the Carr-Purcell-Meiboom-Gill (CPMG) pulse sequence with an echo-time (TE) of about 25 µs. The experimental CPMG curves were best analyzed by a combination of double exponential functions [37,38].…”
Section: Single Sided 1 H Nuclear Magnetic Resonance Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…[47,48] On the other hand, shrinkage behaviour is related to collagen hydrothermal destabilisation and conversion to gelatin, [18,49] while at glass transition temperature, collagen changes from the glassy (crystalline) to the rubbery (amorphous) state. [19,46,50]…”
Section: Parchmentmentioning
confidence: 99%
“…Although NMR has already gained a great deal of importance in the study of heritage materials, [12,13] only a few studies have been conducted to characterise historical and archaeological parchment and leather. NMR spectroscopy was used with particular attention to the degradation processes triggered by the presence of water and thermal conditions, [14][15][16][17][18][19][20] as well as for characterising commercial vegetable tannins extracts [21,22] and modern tanned leathers. [23] In literature, only two studies were focused on the identification of tannins in historical leather by NMR spectroscopy.…”
Section: Introductionmentioning
confidence: 99%